Strategi Guru Agama Dalam Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran Agama Di SDIT Kuala Lama Kecamatan Pantai Cermin - Sri Rahma Aulia Lubis; Ahmad Ridwan; Fathul Jannah (Journal of Innovative and Creativity, 2026)
This study aims to explore students' learning interest in Islamic Religious Education (PAI) subjects, the strategies employed by teachers to enhance that interest, and the supporting and inhibiting factors influencing those strategies at SDIT Kuala Lama, Pantai Cermin District. The research employed a qualitative approach with a descriptive method. Data collection techniques included interviews, observation, and documentation. The subjects of the study consisted of the school principal, Islamic Education teachers, and students from grades V and VI. The findings revealed that students’ interest in learning Islamic Religious Education was categorized as high. This was evidenced by their enthusiasm during lessons, active participation in religious activities, and eagerness to comprehend the material. Teachers applied various strategies to foster interest, such as interactive lectures, group discussions, visual media, and emotional-spiritual approaches. Supporting factors included a religious school environment, strong leadership from the principal, and parental involvement. Meanwhile, inhibiting factors involved limited learning facilities, constrained instructional time, and the diverse learning abilities of students. It can be concluded that students’ learning interest in Islamic Religious Education is closely linked to teachers’ creative and adaptive strategies, as well as a supportive environment that nurtures students’ emotional and spiritual growth. These findings highlight the importance of holistic and engaging approaches in religious education to sustain and increase student interest.